Testing of Model Water Chiller System with Hidrokarbon as a Primer Refrigeran - Suarnadwipa, Nengah; Astawa, Ketut (Jurnal Energi Dan Manufaktur, 2012)
Now days, there are two issues that give a negative impact on the environment due to the uses of synthetic refrigerant on therefrigeration system and air conditioning system. The first issue was the Ozon Layer Depletion and the second issue was theGlobal Warming. Regarding those condition, it will be investigated the design and examination of performance the use of thesplit type AC system as water chiller system and using hydrocarbon as a primer refrigerant. As a result, in the examination ofthe standard split type AC system using refrigerant R-22, it founded that the cooling rate of 1958 Watt and COP of 5.29.While the examination on the modified split type AC system into water chiller system using hydrocarbon (hycool 22), hasgiven cooling rate of 1832 Watt and COP of 4.19. Finally, it could be councluded that the split type AC system could be usedas water chiller system.
Keywords: Split type AC system, Water chiller system, R-22, Hycool-22, Cooling rate, COP.